Review of the genus Diplazon Nees, 1819 (Hymenoptera: Ichneumonidae: Diplazontinae) from Japan - Morishita, Shunsuke; Watanabe, Kyohei (Zootaxa, 2021)
Japanese species of the genus Diplazon Nees, 1819 are reviewed. Nine species are identified from Japan and one of them, D. pallicoxa Manukyan, 1987 is newly recorded. The distribution records of D. orientalis (Cameron, 1905) and D. tibiatorius (Thunberg 1822) are removed from the Japanese fauna. A key to Japanese species of this genus is provided.